Best Answer

the equation is 5(a+2) if a is 1 than the answer is 15

if a is 2 than the answer is 20

if a is 3 than the answer is 25

etc...

Study guides

☆☆

Q: What is the answer to 5 open parenthesis a plus 2 close parenthesis?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x2y2)3 + (x3y3)2 = 2x6y6.

You are given: G(x) = x2 + x So if you want to solve G(2), all you need to do is replace all occurrences of "x" with the number 2, then work out what it comes to. G(2) = 22 + 2 ∴G(2) = 4 + 2 ∴G(2) = 6

(16 x 22)2 = (16 x 4)2 = (64)2 = 4096. Always perform the operations inside parenthesis first.

(4x ^2 + 3) + (3x ^2 + 8) = ( 4x^2 + 3x^2 ) + (3+8) = 7x^2 + 11

(y2 - 2) (2y + 5)This is a fine opportunity to apply the FOILmethod of algebra.'FOIL' is a memory word to help you remember how to multiply two binomials ... exactly the task presented here.'FOIL' stands for 'First', 'Outside', 'Inside', 'Last'. Those are the four pairs of terms you have to multiply, and then add the four products together.First: (y2...) (2y...) = 2y3Outside: (y2...) (... +5) = 5y2Inside: (... -2) (2y... ) = -4yLast: (... -2) (... +5) = -10Add all 4 results, and there you have it: 2y3 + 5y2- 4y - 10

Related questions

(x2y2)3 + (x3y3)2 = 2x6y6.

(\_/)(^_^)(") (")This bunny looks best in Geneva on Microsoft word.DIRECTIONS1. open parenthesis (shift+9) + backward slash + underscore (shift + dash) + forward slash + close parenthesis (shift+0)2. open parenthesis + carat (shift+6)+underscore+carat+close parenthesis3. open parenthesis + quotes (shift + apostrophe) + space + quotes + close parenthesis--or--(\(\('.')(( )( )This bunny looks best in Times New Roman on Microsoft Word.DIRECTIONS:1. open parenthesis (shift+9)+backward slash + open parenthesis + backward slash2a. open parenthesis + open quote + space + open quote + close parenthesis2b. go back to step 2a. and change the space to a period.3. open parenthesis + open parenthesis + space + close parenthesis + open parenthesis + space + close parenthesis

You are given: G(x) = x2 + x So if you want to solve G(2), all you need to do is replace all occurrences of "x" with the number 2, then work out what it comes to. G(2) = 22 + 2 ∴G(2) = 4 + 2 ∴G(2) = 6

(a^2+7a-8)/(a^2+6a-7) (original equation) (a+8)(a-1)/(a+7)(a-1) (simplify top and bottom) (a+8)/(a+7) <--answer

y + 12 = -3(x - 2) y + 12 = -3x + 6 y = -3x - 6 or y = -3(x + 2)

(16 x 22)2 = (16 x 4)2 = (64)2 = 4096. Always perform the operations inside parenthesis first.

(4x ^2 + 3) + (3x ^2 + 8) = ( 4x^2 + 3x^2 ) + (3+8) = 7x^2 + 11

-2(x+4) = -2x-8

(y2 - 2) (2y + 5)This is a fine opportunity to apply the FOILmethod of algebra.'FOIL' is a memory word to help you remember how to multiply two binomials ... exactly the task presented here.'FOIL' stands for 'First', 'Outside', 'Inside', 'Last'. Those are the four pairs of terms you have to multiply, and then add the four products together.First: (y2...) (2y...) = 2y3Outside: (y2...) (... +5) = 5y2Inside: (... -2) (2y... ) = -4yLast: (... -2) (... +5) = -10Add all 4 results, and there you have it: 2y3 + 5y2- 4y - 10

If you mean: y = 3(-3/2)2+9(-3/2)-8 Then: y = -59/4 or as -14.75

It depends on the answer. The parenthesis' placement can change the answer to the problem.

The answer to 6 divided by 2 parenthesis 1 plus 2 is nine. The problem is solved by first adding the numbers in the parenthesis (1 + 2 = 3). Next divide the number 6 by 2 (6/2 = 3) lastly multiply 3 by 3 which gives you 9.